Room-temperature creep deformation of cubic ZnS crystals under controlled light conditions. (15th August 2020) - Oshima, Yu; Nakamura, Atsutomo; Lagerlöf, K.Peter D.; Yokoi, Tatsuya; Matsunaga, Katsuyuki
Abstract: Room-temperature creep tests of ZnS single crystals were conducted along the [001] direction under controlled light conditions in order to investigate the effect of light irradiation on the dislocation motion in ZnS. ZnS crystals stably deform by creep even at room temperature if the tests are conducted in complete darkness. It was found that the strain rate during a creep test can be immediately reduced by irradiating the sample with light having wavelengths of 365 nm or 436 nm even for the case when a sufficient density of mobile dislocations has been introduced due to preceding creep deformation. Surprisingly, the drop in strain rate by the light irradiation was several orders of magnitude. This drop in strain rate is believed to be due to a drastic decrease in the density of mobile dislocations, as well as the mobility of such dislocations, which are derived from the interaction with light-induced electrons and holes. It's also important to note that a significant incubation time appears when creep deformation resumes in the dark (light off) followed by loading under light irradiation during which the creep deformation is very small. This indicates that the light-induced free electrons and holes have long lifetimes in ZnS and, therefore, the existing dislocations continue interacting with electronic defects for several minutes after the light has been turned off. Graphical abstract: Image, graphical abstract